Antiaging Factor Klotho Retards the Progress of Intervertebral Disc Degeneration through the Toll-Like Receptor 4-NF-κB Pathway. (19th March 2020) - Bi, Fangfang; Liu, Wenbo; Wu, Zongtao; Ji, Chen; Chang, Cuicui
Abstract : Antiaging protein Klotho exhibits impressive properties of anti-inflammation, however is declined early after intervertebral disc injury, making Klotho restoration an attractive strategy of treating intervertebral disc inflammatory disorders. Here, we have found that Klotho is enriched in nucleus pulposus (NP) cells and Klotho overexpression attenuates H2 O2 -induced acute inflammation essentially via suppressing Toll-like receptor 4 (TLR4). The proinflammatory NF- κ B signaling and cytokine expressions paralleled with Klotho repression and TLR4 elevation in both NP cells (H2 O2 treatment) and rat intervertebral disc (needle puncture treatment). Overexpression of TLR4 downregulated expression of Klotho, whereas interfering TLR4 expression diminished the inhibitory effects of H2 O2 on Klotho in NP cells. Consistently, Klotho knockdown by RNA interferences largely diminished the anti-inflammatory and intervertebral disc protective effects in an Intervertebral Disc Degeneration (IDD) model. Thus, our study indicates that TLR4-NF- κ B signaling and Klotho form a negative-feedback loop in NP cells. Also, we demonstrate that the expression of Klotho is regulated by the balance between upregulation and downregulation of TLR4-NF- κ B signaling.